2022
DOI: 10.1039/d2nj03332a
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performances of low concentration electrolytes via dual interfacial modification of the fluoroethylene carbonate solvent and lithium difluoro(oxalato)borate additive

Abstract: The high price of lithium salts hinders the sustainable development of high concentration electrolytes, while the poor electrochemical performance limits the large-scale application of low concentration electrolytes. Herein, the electrochemical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…As reported, a stable SEI is established as a prerequisite for realizing the practical application of silicon-based anode cells. Thus, various types of electrolyte additives which are usually able to preferentially form stable SEI on the anode surface before the decomposition of electrolyte body are used in Si-based LIBs. , It is reported that additives of fluoroethylene carbonate (FEC), vinyl carbonate (VC), (pentafluoro­phenyl)­borane (TPFPB), lithium bis­(oxalate)­borate (LiBOB), and lithium difluorobisoxalate phosphate (LiDFBOP) have shown positive effects on improving the cycle life of Si-based anodes. FEC has once been considered as the most promising additive because its reduction products are mainly composed of polyolefins and LiF, and its derived SEI has characteristics of flexibility and high ionic conductivity. However, FEC will decompose at high temperature to generate gaseous products, especially HF, which is very destructive to cycling and safety performances .…”
Section: Introductionmentioning
confidence: 99%
“…As reported, a stable SEI is established as a prerequisite for realizing the practical application of silicon-based anode cells. Thus, various types of electrolyte additives which are usually able to preferentially form stable SEI on the anode surface before the decomposition of electrolyte body are used in Si-based LIBs. , It is reported that additives of fluoroethylene carbonate (FEC), vinyl carbonate (VC), (pentafluoro­phenyl)­borane (TPFPB), lithium bis­(oxalate)­borate (LiBOB), and lithium difluorobisoxalate phosphate (LiDFBOP) have shown positive effects on improving the cycle life of Si-based anodes. FEC has once been considered as the most promising additive because its reduction products are mainly composed of polyolefins and LiF, and its derived SEI has characteristics of flexibility and high ionic conductivity. However, FEC will decompose at high temperature to generate gaseous products, especially HF, which is very destructive to cycling and safety performances .…”
Section: Introductionmentioning
confidence: 99%
“…5g). 25 Additives compete with Li + for the solvent or with the solvent for Li + , indirectly weakening the interaction between Li + and solvent, and promoting the Li + desolvation process. Based on the above strategy, we believe that weakening the strong interaction between Li + and traditional solvents is the key to promoting Li + desolvation.…”
Section: Additives Indirectly Adjusting the Desolvation Processmentioning
confidence: 99%
“…Jiang et al 24 found that LiFSI additives are conducive to reducing to form an inorganic-rich EEI film, which effectively inhibits the continuous reaction between the electrolyte and the Li electrode, prolonging the operation life of the battery. In addition, lithium difluoro(oxalato)borate (LiODFB), 25 lithium difluorophosphate dioxalate (LiDFBOP), 26 lithium difluorophosphate (LiDFP) 27 and other LATAs have also been reported to be able to preferentially decompose to form a dense and stable EEI film. So, film-forming additives have been considered as an effective method to adjust the performance of the EEI film.…”
Section: Anion-solvated Complex Regulating Eei Film Componentsmentioning
confidence: 99%